MARMARAY BOSPHORUS CROSSING PROJECT: SURVEYING ACTIVITY AND GEODETIC MONITORING - Gulal, Engin (UNIV OSIJEK, TECH FAC, 2014)
The ongoing Marmaray Project is one of the largest transportation infrastructure projects in the world. The total length of the over ground and underground Marmaray project is 76,7 km. The first part of project is the Bosphorus Crossing (BC1) with a length of 13,6 km. The BC1 project contains the construction of three bored tunnels and immersed tunnel under the Istanbul Strait. The construction studies in the tunnels and immersing tube were completed in the beginning of 2012. The planning and design of engineering projects are the main study focus of the engineering survey which is a basic requirement for many engineering projects. This paper explains the recent advances in engineering surveying operations, such as establishing the geodetic control network, deformation monitoring and as-built surveys, in the scope of BC1 project. The experiences gained during the measurement studies are presented as a guide for similar projects that will be realized in the future.
Keywords: geodetic monitoring; Marmaray; surveying; tunnel; Engineering